Investigation of iron’s neurotoxicity during cerebral maturation in the neonatal rat model of haemolysis - Akar, Ebru; Ünalp, Aycan; Diniz, Gulden; Ortac, Ragip; Senturk, Banu; Yilmaz, Osman; Kiray, Muge; Tepetam, Merve; Coker, Canan; Cangar, Sukru (Folia Neuropathologica, 2015)
Introduction : Haemolytic disease of newborns due to rhesus and AB0 incompatibility is encountered frequently in neonatal clinics and may lead to severe haemolysis. In this study, it is suggested that important amounts of iron released with haemolysis may have a toxic effect on the brain parenchymal tissue, and the severity of the toxic effect can be correlated with the maturation of the brain barrier systems. To demonstrate the accumulation and the neurotoxic effects of free iron (Fe) in the brain an experimental haemolysis model with various maturation phases was performed. Material and methods: The study was composed of 48 Wistar rats with the following ages: five days old (Group A), 10 days old (Group B), and 19 days old (Group C). Each group was divided into three experimental subgroups and three control groups. Experimental groups were treated with intraperitoneal 75 mg/kg/day phenyl hydrazine hydrochloride for haemolysis. Results : We demonstrated that the blood brain barrier (BBB) is permeable in five-day-old newborn rats and is mature in 10- and 19-day-old rats. Iron staining and neuronal damage were detected in group A and group B rats. No damage was detected in the brain tissue of group C animals. The presence of iron staining and neuronal damage in group B with mature BBB may suggest the existence of other incomplete barrier systems different from BBB that lead to iron accumulation in the brain. Conclusions : Blood brain barrier has a partial role in Fe transport, and the alternative barrier systems may also be involved. It could be supposed that after maturation of all barrier systems, excessive Fe penetration to the brain cannot occur. Our findings showed that the toxic amounts of iron may penetrate into the brain parenchyma of newborns despite the BBB preservation and cause neuronal damage in newborns, but the mature brain is not affected by the same magnitude blood levels.